1993
DOI: 10.1627/jpi1958.36.472
|View full text |Cite
|
Sign up to set email alerts
|

Derivation of PVT Correlations for the Gulf of Suez Crude Oils.

Abstract: Proper evaluation of physical properties of hydrocarbon mixtures is a prerequisite for the design of various stages of oil field operations.In many cases these properties are required at a time when the only information available consists of oil and gas gravities and reservoir pressure and temperature. The purpose of this study is to utilize a sufficient base of laboratory-measured PVT data to derive specific empirical correlations for the prediction of the saturation pressure Pb, gas in solution Rs and tool i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(13 citation statements)
references
References 4 publications
0
11
0
1
Order By: Relevance
“…Each study claimed that the resulting correlation would provide the best approximation of PVT properties for the local region compared to the other commonly used correlations. Studies performed by El-hoshoudy et al [4] ,Macary and Batanony [5],Hanafy et al [6], Glasso [7] ,Dokla and Osman [8] ,Marhoun [2], Labedi [9] all supported this conclusion [5]. Multiple linear/nonlinear least-squares regression analysis will be used to develop the new correlations after screening of the used parameters.…”
Section: Introductionmentioning
confidence: 84%
“…Each study claimed that the resulting correlation would provide the best approximation of PVT properties for the local region compared to the other commonly used correlations. Studies performed by El-hoshoudy et al [4] ,Macary and Batanony [5],Hanafy et al [6], Glasso [7] ,Dokla and Osman [8] ,Marhoun [2], Labedi [9] all supported this conclusion [5]. Multiple linear/nonlinear least-squares regression analysis will be used to develop the new correlations after screening of the used parameters.…”
Section: Introductionmentioning
confidence: 84%
“…Figure 5 illustrates graphically the calculated AARD for the model developed, as well as all comparative methods investigated in the study. From Table 2 and Figure 5, it can be concluded that the methods of Baniasadi et al [42], Al-Shammasi [55], Macary and El-Batanony [53], Dindoruk and Christman [56], and Al-Marhoun [9] are, after the method proposed in this study, the most accurate for the calculation of solution GOR with AARD values of 23.15, 32.95, 36.54, 36.89, and 42.01%, respectively. Table 3 lists some random data points selected from the databank, and Table 4 summarizes the estimated values for the data points presented in Table 3 using method developed and empirical methods discussed above.…”
Section: Performance Evaluation Of the New Modelmentioning
confidence: 92%
“…A comprehensive comparison analysis was undertaken between the model developed in this study and widely-used empirically derived methods including the Farshad et al method [2], Macary and ElBatanony method [53], Petrosky and Farshad method [24], Vazquez and Beggs method [16], Al-Marhoun method [9], Kartoatmodjo and Schmidt method [54], Al-Shammasi method [55], Standing method [23], Glaso [20], Baniasadi et al method [42], and Dindoruk and Christman method [56] in order to evaluate the performance of the method in predicting solution GOR data. Table 2 reports the statistical results obtained for the comparisons undertaken.…”
Section: Performance Evaluation Of the New Modelmentioning
confidence: 99%
“…Dokla and Osman (1992) presented a set of correlations based on 51 bottom-hole samples from United Arab Emirates reservoirs. Macary and El-Batanoney (1993) developed correlations based on 90 experimentally measured data from 30 independent Egyptian reservoirs. The bubblepoint correlation of Kartoatmodjo and Schmidt (1994) was developed based on 5,392 data points from 740 PVT samples from South East Asia, North America, the Middle East and Latin America.…”
Section: Models Through Commonly Available Field Datamentioning
confidence: 99%